Two new species of the genus Xizicus Gorochov, 1993 (Orthoptera: Tettigoniidae: Meconematinae) from south China - Wen, Mingye; Ren, Bingyu; Shi, Fuming; Chang, Yanlin (Zootaxa, 2025)
The paper reports 2 new species of the genus Xizicus Gorochov, 1993 from China, i.e. Xizicus (Eoxizicus) hamatus sp. nov. and Xizicus (Eoxizicus) brevicaudus sp. nov., and supplies characteristic photographs of external morphology. The type specimens are deposited in the Museum of Hebei University, Baoding, P. R. China.